(untitled) (Research, Society and Development, 2021)
To investigate the effects of tamoxifen on Staphylococcus aureus α-hemolysin channel (α-HL) in planar lipid bilayers with electrophysiological characterization and docking studies. Planar lipid bilayer membranes were prepared and α-HL (0.07 mg/mL) was added to the standard solution in cis compartment of the experimental chamber. All experiments were performed at room temperature using an Axopatch 200A amplifier in the voltage clamp mode. At pH 7.5, α-HL channels were usually in a high conductance 4 nS and rarely switch to low conductance states. After the ion channel was incorporated in bilayer membrane, the tamoxifen was also added to the standard solution to the cis compartment. To docking studies, atomics coordinates for the α-HL heptameric channel was retrieved from PDB ID (7AHL) and the structure of tamoxifen was removed from the Pubchem, their coordinates were built and minimized with Avogadro software. The molecular docking experiments were performed using the Dockthor online portal. The tamoxifen inhibited (P < 0.05) α-HL channel conductance and it was a voltage-dependent manner. The three best docking solutions and the α-HL channel were evaluated, it was observed the connection mode with the highest affinity of interaction has a greater number of types of polar interaction. The residues present interactions of greater energy were 111 and 147 that form the remainders of the constriction in the channel of α-HL. The other conformers were accommodated in a region with more hydrophobic characteristics (valine 149). The mechanism of Staphylococcus aureus α-hemolysin inhibition by tamoxifen was blockade over the constriction of channel.